The effect of planting distance engineering treatment on the morphophysiology and yield of soybean varieties integrated with oil palm - WAGINO WAGINO; ABDUL RAUF; CHAIRANI HANUM; RAHMANTA RAHMANTA (Society for Indonesian Biodiversity, 2024)
Abstract. Wagino, Rauf A, Hanum C, Rahmanta. 2024. The effect of planting distance engineering treatment on the morphophysiology and yield of soybean varieties integrated with oil palm. Biodiversitas 25: 3909-3919. The use of inter-land in oil palm plantations of immature plants is commonly studied, and the use in productive oil palm plantations distance has not been investigated. The research aimed to evaluate the productivity, environmental characteristics, and economic value of oil palm and soybean integration. A Split-Plot Design was used with the main plot consisted oil palm planting, the sub-plot was soybean planting repeated three times. The results that light intensity unmodified oil palm planting distance system decreased by 28% compared to the modified. The treatment of oil palm planting distance modification had a significant effect on the amount of leaf chlorophyll, seed weight per plant (11.49 g), weight of 100 seeds (18.29 g), production per-plot (993.55 g), and Dena 1 (692.90 g). The Land Equivalency Ratio (LER) was >1 (1.06) integration of Dena 1 soybean variety with oil palm planting distance engineering and an R/C value of 1.79, providing greater benefits compared to the monoculture planting system. The system also provided improvements to the environment by an increase in nitrogen (N) nutrient levels and soil organic carbon (C) levels. The oil palm planting distance engineering model could be a solution to increase sustainable soybean production in Indonesia.